Preparation method of nitrogen-doped reduced graphene oxide / cellulose asymmetric modified diaphragm for lithium-sulfur battery
By using nitrogen-doped to reduce graphene oxide and cellulose on lithium sulfur battery separators, the shortcomings of existing separators in capturing lithium polysulfide and inhibiting dendrites are solved, and efficient electrochemistry is achieved Energy storage and stable circulation performance.
Patent Information
- Application Number
- CN202411679473.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing lithium-sulfur battery separator materials are difficult to effectively capture lithium polysulfide, and the modification process on the negative electrode side of the metal lithium is complex, which limits the development and application of lithium-sulfur batteries.
Asymmetrically modified separator by applying nitrogen-doped reducing graphene oxide/cellulose asymmetrically modified by coating nitrogen-doped reducing graphene oxide on the positive electrode side of the separator to adsorption and catalyzing lithium polysulfide conversion, and applying cellulose on the negative electrode side to inhibit Dentite growth.
The high discharge specific capacity and cycle stability of lithium-sulfur batteries are achieved, the preparation process of the diaphragm is simplified, and the cost is reduced, and the application potential of large-scale electrochemical energy storage is achieved.
Smart Images

Figure CN119481574A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium-sulfur battery diaphragm materials, and in particular relates to a method for preparing a nitrogen-doped reduced graphene oxide / cellulose asymmetric modified diaphragm for a lithium-sulfur battery. Background Art
[0002] With the development of economy, the demand for energy in society is gradually increasing, and the relationship between human beings and energy is becoming closer. The use of secondary batteries to achieve efficient conversion and utilization of energy is a hot topic in today's social research. Lithium-ion batteries, as a secondary battery, have been widely used in energy vehicles, portable devices and other fields. However, their further development is limited by their low theoretical energy density. As a new type of secondary battery, lithium-sulfur batteries have the characteristics of low cost, high discharge platform, high theoretical capacity and high energy density, and are considered to have great development potential.
[0003] At present, the main materials for modifying the diaphragm of lithium-sulfur batteries are carbon materials, polymer materials and inorganic catalyst materials. In contrast, carbon materials are considered to be one of the candidates for diaphragm modification materials because of their advantages such as light weight, porosity, high specific surface area and high conductivity. However, due to the non-polar characteristics of carbon materials themselves, it is difficult to capture lithium polysulfide through chemical interactions, and the shuttling of lithium polysulfide can only be inhibited by physical effects. Simple heteroatom doping of carbon materials can play a role in adsorbing and catalyzing the conversion of lithium polysulfide. For the modification of the negative electrode side of metallic lithium, complex material preparation processes and the introduction of a large amount of active materials are usually required to inhibit the growth of dendrites. The above problems seriously limit the development and practical application of lithium-sulfur batteries, and there is an urgent need to develop a modified diaphragm that is simple and easy to prepare and can solve the problems of both positive and negative electrodes. Summary of the invention
[0004] In view of the above problems currently existing in lithium-sulfur batteries, the present invention provides a method for preparing a nitrogen-doped reduced graphene oxide / cellulose asymmetric modified diaphragm for lithium-sulfur batteries. The modified diaphragm prepared by this method has the advantages of low cost, simple preparation process and excellent structural stability, and the assembled battery has good cycle stability and high discharge specific capacity, thus having the application potential of large-scale electrochemical energy storage.
[0005] The method for preparing the nitrogen-doped reduced graphene oxide / cellulose asymmetric modified diaphragm of the present invention comprises the following steps: Step 1: Disperse graphite powder and sodium nitrate in deionized water, add concentrated sulfuric acid solution, and then add potassium permanganate powder; then heat the mixture, and after the reaction is completed, add excess hydrogen peroxide solution to the system to remove the incompletely reacted potassium permanganate, and wash with deionized water for multiple times until the pH value of the upper solution reaches a weak acid; freeze-dry the washed product to obtain graphene oxide powder.
[0006] Step 2: dissolving ammonium chloride in deionized water to obtain an ammonium chloride solution; adding the graphene oxide powder obtained in step 1 to the ammonium chloride solution and ultrasonically stirring; freeze-drying the obtained product to obtain a mixed powder of graphene oxide and ammonium chloride.
[0007] Step 3: The mixed powder of graphene oxide and ammonium chloride obtained in step 2 is subjected to high-temperature heat treatment in a nitrogen atmosphere, and after naturally cooling to room temperature, nitrogen-doped reduced graphene oxide is obtained, which is denoted as N-rGO and used as the active material on the positive electrode side of the modified diaphragm.
[0008] Step 4: Use commercially available cellulose powder, denoted as CF, as the active material on the negative electrode side of the modified separator.
[0009] Step 5: The nitrogen-doped reduced graphene oxide obtained in step 3 is used as an active material, mixed with a binder and Ketjen black in a certain proportion, and coated on one side of the diaphragm; the cellulose obtained in step 4 is used as an active material, mixed with a binder and coated on the other side of the diaphragm to prepare a nitrogen-doped reduced graphene oxide / cellulose asymmetric modified diaphragm, recorded as N-rGO@PP@CF.
[0010] Preferably, in step 1, the concentration of concentrated sulfuric acid is 95.0-98.0%; the amount ratio of graphite powder, sodium nitrate, potassium permanganate, deionized water, and concentrated sulfuric acid solution is 2.0-2.5 g: 1.2-1.5 g: 8.0-10.0 g: 120-150 mL: 50-60 mL. The concentration of hydrogen peroxide is ≥30.0%.
[0011] Preferably, in step 1, the heating reaction temperature is 80° C. and the reaction time is 2 h.
[0012] Preferably, in step 1, washing is performed with deionized water until the pH value of the upper layer solution reaches 3.0-4.0.
[0013] Preferably, in step 2, the usage ratio of graphene oxide, ammonium chloride and deionized water is 0.8~1.0 g:4.0~5.0 g:80~100 mL.
[0014] Preferably, in step 2, the ultrasonic stirring time is 4 to 5 h.
[0015] Preferably, in step 3, the heat treatment temperature is 600-800° C., the heat treatment time is 1-2 h, and the heating rate is 5° C. / min.
[0016] Preferably, in step 5, the mass ratio of nitrogen-doped reduced graphene oxide, binder and Ketjen black is 8:1:1; the mass ratio of cellulose to binder is 4:1. The binder is polyvinylidene fluoride.
[0017] Preferably, in step 5, the diaphragm is a commercial polypropylene (PP) diaphragm, and the coating thickness of the slurry on both sides of the diaphragm is ≤3 μm.
[0018] The present invention also provides a lithium-sulfur battery, wherein the lithium-sulfur battery is assembled by using the nitrogen-doped reduced oxide graphene / cellulose asymmetric modified diaphragm.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention prepares an asymmetric modified diaphragm by coating active materials on both sides of the diaphragm respectively, coating nitrogen-doped reduced graphene oxide on the positive electrode side of the diaphragm to adsorb and catalyze the conversion of lithium polysulfide, and coating cellulose on the negative electrode side of the diaphragm to achieve uniform metallic lithium deposition and inhibit dendrite growth. Different from traditional modified diaphragms, the use of an asymmetric modified diaphragm can interact with the positive and negative electrodes at the same time, so the assembled battery has high discharge specific capacity and cycle stability.
[0020] The preparation process of the invention is simple and low-cost, and large-scale preparation is possible, which is conducive to the development of high-performance lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a scanning electron microscope image of the CF of Example 1 of the present invention. Figure 1 As can be seen from the figure, CF presents a three-dimensional structure.
[0022] Figure 2 is a scanning electron microscope image of N-rGO prepared in Example 2 of the present invention. Figure 2 It can be seen that the morphology of N-rGO is a two-dimensional lamellar structure with a size of approximately 5~20 μm.
[0023] Figure 3 This is a high-resolution transmission electron microscopy image of N-rGO prepared in Example 2 of the present invention. Figure 3 As can be seen in the figure, N-rGO exhibits a two-dimensional lamellar structure, indicating that graphite is effectively exfoliated.
[0024] Figure 4 is the element distribution diagram of N-rGO prepared in Example 2 of the present invention. Figure 4 It can be seen that the three elements C, N and O are evenly distributed on N-rGO.
[0025] Figure 5 is the X-ray photoelectron spectrum of N-rGO prepared in Example 2 of the present invention. Figure 5 It can be seen that the peaks of the N 1s spectrum at 398.36, 399.30, and 401.32 eV correspond to pyridinic nitrogen, pyrrolic nitrogen, and graphitic nitrogen, respectively.
[0026] Figure 6 The cycle performance diagram of the symmetrical battery assembled by CF@PP@CF prepared in Example 1 of the present invention. Figure 6 It can be seen that the battery assembled with CF@PP@CF separator has a high conductivity at 1 mA / cm 2 The current density and 1 mAh / cm 2 The battery can be cycled stably for 950 h at a capacity of 1.
[0027] Figure 7 The morphology of the lithium negative electrode of the symmetrical battery assembled from CF@PP@CF prepared in Example 1 of the present invention after cycling. Figure 7 As can be seen from the figure, the battery assembled with CF@PP@CF separator has a high conductivity at 2 mA / cm 2 The current density and 1 mAh / cm 2 After 100 cycles at a capacity of , it can be found that there is no obvious dendrite formation on the surface of the metal lithium negative electrode after the cycle and the deposition of metal lithium is relatively uniform and dense.
[0028] Figure 8 The electrochemical impedance spectrum of the symmetrical battery assembled from CF@PP@CF prepared in Example 1 of the present invention. Figure 8 It can be seen that the battery assembled using CF@PP@CF separator has lower charge transfer impedance.
[0029] Fig. 9 The optical photos and UV images of N-rGO and rGO after adsorption of Li2S6 in Examples 2 and 3 of the present invention are shown. Fig. 9 It can be seen that both N-rGO and rGO have adsorption effects on Li2S6, but the adsorption effect of N-rGO on Li2S6 is stronger.
[0030] Fig.10 This is a cross-sectional view of the diaphragm modified from Example 4 of the present invention. Fig.10 It can be seen that N-rGO and CF are coated on both sides of the separator and the coating thickness is less than 3 μm.
[0031] Fig.11 The cyclic voltammetry curve of the full battery assembled by N-rGO@PP@CF prepared in Example 4 of the present invention and rGO@PP@CF prepared in Example 5. Fig.11It can be seen that the battery assembled using N-rGO@PP@CF membrane has a larger current density and smaller voltage hysteresis than the battery assembled using rGO@PP@CF membrane.
[0032] Fig.12 The cycle performance diagram of the full battery assembled by N-rGO@PP prepared in Example 2 of the present invention and rGO@PP prepared in Example 3. Fig.12 It can be seen that the battery assembled with N-rGO@PP separator has a higher discharge specific capacity than the battery assembled with rGO@PP separator, indicating that N-rGO has a stronger adsorption and catalytic effect on lithium polysulfide than rGO.
[0033] Fig.13 The cycle performance diagram of the full battery assembled by N-rGO@PP@CF prepared in Example 4 of the present invention and rGO@PP@CF prepared in Example 5. Fig.13 It can be seen that the battery assembled with N-rGO@PP@CF membrane has a higher discharge specific capacity than the battery assembled with rGO@PP@CF membrane. Fig.12 In terms of performance, the diaphragm modified with CF has better performance, indicating that CF can reduce the contact area between lithium polysulfide and the negative electrode by uniformly depositing the morphology of the metallic lithium negative electrode, thereby reducing the loss of active substances.
[0034] Fig.14 The figure is the rate performance diagram of the full battery assembled by N-rGO@PP@CF prepared in Example 4 of the present invention and rGO@PP@CF prepared in Example 5. Fig.14 It can be seen that the battery assembled with N-rGO@PP@CF membrane has higher discharge specific capacity at different currents than the battery assembled with rGO@PP@CF membrane.
[0035] Fig.15 The charge and discharge curve of the full battery assembled by N-rGO@PP@CF prepared in Example 4 of the present invention. Fig.15 It can be seen that the battery assembled with N-rGO@PP@CF separator has a stable discharge platform at different currents. DETAILED DESCRIPTION
[0036] To further illustrate the present invention, a method for preparing a nitrogen-doped reduced graphene oxide / cellulose asymmetric modified diaphragm for a lithium-sulfur battery provided by the present invention is described in detail below in conjunction with an embodiment. The described embodiment is only a part of the embodiments of the present invention, but not all of them. Embodiment 1:
[0037] In this example, the cellulose / cellulose modified membrane was prepared according to the following steps: Step 1: Use commercially available cellulose powder, denoted as CF, as the active material on the positive and negative electrode sides of the modified diaphragm.
[0038] Step 2: The CF and polyvinylidene fluoride obtained in step 1 are prepared into a slurry at a mass ratio of 4:1, and coated on both sides of the diaphragm to finally prepare a cellulose / cellulose modified diaphragm, which is recorded as CF@PP@CF. Embodiment 2:
[0039] In this embodiment, the nitrogen-doped reduced graphene oxide modified diaphragm is prepared according to the following steps: Step 1. Place 2.5 g of graphite powder and 1.5 g of sodium nitrate in a round-bottom flask and add 150 mL of deionized water. Measure 60 mL of concentrated sulfuric acid and slowly inject it into the flask under ice-water bath conditions, while continuously stirring and maintaining a low temperature environment. When the reaction system no longer releases heat significantly, add 10 g of potassium permanganate to the flask. Subsequently, heat the mixture to 80°C and keep it for 2 h. After the reaction is completed, wait for it to cool to room temperature, and then add excess hydrogen peroxide solution to the flask to remove the incompletely consumed potassium permanganate. Wash with deionized water several times until the pH value of the upper solution reaches 3.0~4.0. The washed product is freeze-dried to obtain graphene oxide powder.
[0040] Step 2: Disperse 1 g of graphene oxide powder in 100 mL of deionized water, add 5 g of ammonium chloride thereto, stir ultrasonically for 5 h, and freeze-dry the resulting product for 3 days to obtain a mixed powder of graphene oxide and ammonium chloride.
[0041] Step 3: Place the mixed powder of graphene oxide and ammonium chloride in a tube furnace at 800°C in a nitrogen atmosphere for 2 h at a heating rate of 5°C / min. After cooling naturally to room temperature, nitrogen-doped reduced graphene oxide is obtained, which is recorded as N-rGO and used as the active material on the positive electrode side of the modified separator.
[0042] Step 4: Use the N-rGO obtained in step 3, polyvinylidene fluoride and Ketjen black in a mass ratio of 8:1:1 to prepare a slurry, which is coated on one side of the diaphragm and recorded as N-rGO@PP. Embodiment 3:
[0043] In this embodiment, the reduced graphene oxide modified diaphragm is prepared according to the following steps: Step 1. Place 2.5 g of graphite powder and 1.5 g of sodium nitrate in a round-bottom flask and add 150 mL of deionized water. Measure 60 mL of concentrated sulfuric acid and slowly inject it into the flask under ice-water bath conditions, while continuously stirring and maintaining a low temperature environment. When the reaction system no longer releases heat significantly, add 10 g of potassium permanganate to the flask. Subsequently, heat the mixture to 80°C and keep it for 2 h. After the reaction is completed, wait for it to cool to room temperature, and then add excess hydrogen peroxide solution to the flask to remove the incompletely consumed potassium permanganate. Wash with deionized water several times until the pH value of the upper solution reaches 3.0~4.0. The washed product is freeze-dried to obtain graphene oxide powder.
[0044] Step 2: Place the graphene oxide powder in a tube furnace under a nitrogen atmosphere at 800°C for 2 h at a heating rate of 5°C / min. After cooling naturally to room temperature, reduced graphene oxide is obtained, denoted as rGO, as the active material on the positive electrode side of the modified separator.
[0045] Step 3: Use the rGO obtained in step 2, polyvinylidene fluoride and Ketjen black in a mass ratio of 8:1:1 to prepare a slurry, which is coated on one side of the diaphragm and recorded as rGO@PP. Embodiment 4:
[0046] In this example, the nitrogen-doped reduced graphene oxide / cellulose asymmetric modified membrane was prepared according to the following steps: Step 1. Place 2.5 g of graphite powder and 1.5 g of sodium nitrate in a round-bottom flask and add 150 mL of deionized water. Measure 60 mL of concentrated sulfuric acid and slowly inject it into the flask under ice-water bath conditions, while continuously stirring and maintaining a low temperature environment. When the reaction system no longer releases heat significantly, add 10 g of potassium permanganate to the flask. Subsequently, heat the mixture to 80°C and keep it for 2 h. After the reaction is completed, wait for it to cool to room temperature, and then add excess hydrogen peroxide solution to the flask to remove the incompletely consumed potassium permanganate. Wash with deionized water several times until the pH value of the upper solution reaches 3.0~4.0. The washed product is freeze-dried to obtain graphene oxide powder.
[0047] Step 2: Disperse 1 g of graphene oxide powder in 100 mL of deionized water, add 5 g of ammonium chloride thereto, stir ultrasonically for 5 h, and freeze-dry the resulting product for 3 days to obtain a mixed powder of graphene oxide and ammonium chloride.
[0048] Step 3: Place the mixed powder of graphene oxide and ammonium chloride in a tube furnace at 800°C in a nitrogen atmosphere for 2 h at a heating rate of 5°C / min. After cooling naturally to room temperature, nitrogen-doped reduced graphene oxide is obtained, which is recorded as N-rGO and used as the active material on the positive electrode side of the modified separator.
[0049] Step 4: Use commercially available cellulose powder, denoted as CF, as the active material on the negative electrode side of the modified separator.
[0050] Step 5, using the N-rGO obtained in step 3, polyvinylidene fluoride and Ketjen black in a mass ratio of 8:1:1 to prepare a slurry, and apply it on one side of the diaphragm; using the CF obtained in step 4 and polyvinylidene fluoride in a mass ratio of 4:1 to prepare a slurry, and apply it on the other side of the diaphragm, finally preparing a nitrogen-doped reduced graphene oxide / cellulose asymmetric modified diaphragm, recorded as N-rGO@PP@CF. Embodiment 5:
[0051] In this example, the reduced graphene oxide / cellulose asymmetric modified membrane was prepared according to the following steps: Step 1. Place 2.5 g of graphite powder and 1.5 g of sodium nitrate in a round-bottom flask and add 150 mL of deionized water. Measure 60 mL of concentrated sulfuric acid and slowly inject it into the flask under ice-water bath conditions, while continuously stirring and maintaining a low temperature environment. When the reaction system no longer releases heat significantly, add 10 g of potassium permanganate to the flask. Subsequently, heat the mixture to 80°C and keep it for 2 h. After the reaction is completed, wait for it to cool to room temperature, and then add excess hydrogen peroxide solution to the flask to remove the incompletely consumed potassium permanganate. Wash with deionized water several times until the pH value of the upper solution reaches 3.0~4.0. The washed product is freeze-dried to obtain graphene oxide powder.
[0052] Step 2: Place the graphene oxide powder in a tube furnace under a nitrogen atmosphere at 800°C for 2 h at a heating rate of 5°C / min. After cooling naturally to room temperature, reduced graphene oxide is obtained, denoted as rGO, as the active material on the positive electrode side of the modified separator.
[0053] Step 3: Use commercially available cellulose powder, denoted as CF, as the active material on the negative electrode side of the modified separator.
[0054] Step 4: Use the rGO obtained in step 2, polyvinylidene fluoride and Ketjen black in a mass ratio of 8:1:1 to prepare a slurry, which is applied on one side of the diaphragm; use the CF obtained in step 3 and polyvinylidene fluoride in a mass ratio of 4:1 to prepare a slurry, which is applied on the other side of the diaphragm, and finally prepare a reduced graphene oxide / cellulose asymmetric modified diaphragm, recorded as rGO@PP@CF.
[0055] The full battery in this article uses sulfur as the positive electrode material, lithium metal as the negative electrode, and the embodiment as the separator to assemble into a battery. The symmetric battery uses lithium metal as the positive and negative electrodes, and the embodiment as the separator to assemble into a battery.
[0056] The lithium symmetric battery assembled using Example 1 can be stably cycled for 950 h. The uniform morphology of the metal lithium negative electrode after the cycle shows that CF has the effect of uniform lithium deposition and inhibiting the growth of lithium dendrites. The performance results of the full battery assembled using Examples 2 and 3 show that N-rGO has a stronger adsorption and catalytic effect on lithium polysulfide than rGO. The full battery assembled using Examples 4 and 5, after the experimental results of electrochemical cyclic voltammetry curves, long cycles and rate performance, show that N-rGO and CF can interact with the positive and negative electrodes at the same time, thereby more effectively improving the performance of the battery.
[0057] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nitrogen-doped reduced graphene oxide / cellulose asymmetric modified diaphragm, characterized in that: Nitrogen-doped reduced graphene oxide is used as the active material on the positive electrode side of the modified membrane, mixed with a binder and Ketjen black, and coated on one side of the membrane; cellulose is used as the active material on the negative electrode side of the modified membrane, mixed with a binder and coated on the other side of the membrane, to prepare a nitrogen-doped reduced graphene oxide / cellulose asymmetric modified membrane.
2. The preparation method according to claim 1, characterized in that The steps include: Step 1: Disperse graphite powder and sodium nitrate in deionized water, add concentrated sulfuric acid solution, and then add potassium permanganate powder; then heat the mixture, and after the reaction is completed, add excess hydrogen peroxide solution to the system to remove the incompletely reacted potassium permanganate, and wash with deionized water for multiple times until the pH value of the upper solution reaches a weak acid; freeze-dry the washed product to obtain graphene oxide powder; Step 2: dissolving ammonium chloride in deionized water to obtain an ammonium chloride solution; adding the graphene oxide powder obtained in step 1 to the ammonium chloride solution and stirring with ultrasound; freeze-drying the obtained product to obtain a mixed powder of graphene oxide and ammonium chloride; Step 3: subjecting the mixed powder of graphene oxide and ammonium chloride obtained in step 2 to high temperature heat treatment in a nitrogen atmosphere, and after naturally cooling to room temperature, nitrogen-doped reduced graphene oxide, denoted as N-rGO, is obtained as the active material on the positive electrode side of the modified diaphragm; Step 4: using cellulose powder, denoted as CF, as the active material on the negative electrode side of the modified separator; Step 5: The nitrogen-doped reduced graphene oxide obtained in step 3 is used as an active material, mixed with a binder and Ketjen black in a certain proportion, and coated on one side of the diaphragm; cellulose is used as an active material, mixed with a binder and coated on the other side of the diaphragm to prepare a nitrogen-doped reduced graphene oxide / cellulose asymmetric modified diaphragm, recorded as N-rGO@PP@CF.
3. The preparation method according to claim 2, characterized in that: In step 1, the usage ratio of graphite powder, sodium nitrate, potassium permanganate, deionized water, and concentrated sulfuric acid solution is 2.0-2.5 g: 1.2-1.5 g: 8.0-10.0 g: 120-150 mL: 50-60 mL.
4. The preparation method according to claim 2, characterized in that: In step 1, the heating reaction temperature is 80°C and the reaction time is 2 h.
5. The preparation method according to claim 2, characterized in that: In step 1, the solution is washed with deionized water until the pH value of the upper layer reaches 3.0-4.
0.
6. The preparation method according to claim 2, characterized in that: In step 2, the usage ratio of graphene oxide, ammonium chloride and deionized water is 0.8~1.0 g:4.0~5.0 g:80~100 mL.
7. The preparation method according to claim 2, characterized in that: In step 3, the heat treatment temperature is 600-800°C, the heat treatment time is 1-2 h, and the heating rate is 5°C / min.
8. The preparation method according to claim 2, characterized in that: In step 5, the mass ratio of nitrogen-doped reduced graphene oxide, binder and Ketjen black is 8:1:1; the mass ratio of cellulose to binder is 4:
1.
9. A lithium-sulfur battery, obtained by assembling a nitrogen-doped reduced graphene oxide / cellulose asymmetric modified diaphragm prepared by the preparation method of any one of claims 1 to 8.
Citation Information
Patent Citations
Nitrogen doped graphene material and preparation method thereof
CN102757029A
Lithium sulfur storage battery
CN104124413A
Asymmetric diaphragm and application thereof in lithium-sulfur rechargeable battery
CN105261721A
Battery diaphragm and preparation method thereof and lithium-sulfur battery
CN105609690A
Lithium-sulfur battery taking nitrogen-doped foamy graphene sheet as middle layer, and preparation method thereof
CN107887557A